2020
DOI: 10.1002/brb3.1751
|View full text |Cite
|
Sign up to set email alerts
|

Disentangling the relationship between cholesterol, aggression, and impulsivity in severe mental disorders

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 71 publications
0
8
1
Order By: Relevance
“…This is considered to be the most important result of this study. Our results are not in line with the findings obtained in large groups of patients with schizophrenia and bipolar spectrum disorders, where no significant associations between HDL cholesterol levels and aggression or impulsivity were detected [ 21 ]. The level of HDL cholesterol in subjects with and without aggression was tested for the influence of age, primary dose of therapy, smoking, severity of symptoms of schizophrenia and aggression, and the presence of suicidal behavior, by multiple linear regression.…”
Section: Discussioncontrasting
confidence: 99%
“…This is considered to be the most important result of this study. Our results are not in line with the findings obtained in large groups of patients with schizophrenia and bipolar spectrum disorders, where no significant associations between HDL cholesterol levels and aggression or impulsivity were detected [ 21 ]. The level of HDL cholesterol in subjects with and without aggression was tested for the influence of age, primary dose of therapy, smoking, severity of symptoms of schizophrenia and aggression, and the presence of suicidal behavior, by multiple linear regression.…”
Section: Discussioncontrasting
confidence: 99%
“…A total of nine studies ( Cariou et al, 2018 ; Chakrabarti et al, 2004 ; Chen et al, 2015 ; Eriksen et al, 2017 , 2018 ; Hjell et al, 2020 ; Huang and Wu, 2000 ; Repo-Tiihonen et al, 2002 ; Turkoglu et al, 2009 ) explored the link between lipid profile and violence against others, of which six studies found a link. However, there were some variations in the findings.…”
Section: Resultsmentioning
confidence: 99%
“…The studies were again spread over a time period of almost two decades, between 2002 and 2020. Sample sizes varied widely, the largest study with a sample size of 1001 ( Hjell et al, 2020 ), medium level studies with sample sizes of 409 and 348 ( Eriksen et al, 2018 ; Repo-Tiihonen et al, 2002 ) and the smallest with a sample size of 60 patients (Chakrabarti et al, 2009).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations